Analisis Sistem Pengendalian Intern Dalam Efektivitas Pengelolaan Kantor Kas Pada Lembaga Perkreditan Desa (LPD) Desa Adat Tajun - Kadek Widiani; Ni Luh Gede Erni Sulindawati (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the background of the establishment of the cash office, cash office management system, internal control system applied in the management of the cash office, and analyze the effectiveness of the internal control system applied in managing the cash office at LPD Desa Adat Tajun. This research is a qualitative descriptive study. The subject of this research is the LPD Cash Office of the Tajun Traditional Village, while the object of this research is the internal control system in managing the cash office. The data collected in this study used the methods of observation, interviews and documentation. The results of this study indicate that, 1) the background of the formation of a cash office at the LPD of the Tajun Traditional Village is an effort to meet the needs of the community inmaking loans for electronic goods, furniture, and motorcycles seeing the location of the Tajun village which is far from the city center. Improving services to the community, and providing what is not yet available in the Tajun village. 2) The cash office management system at the Tajun Traditional Village LPD goes through several stages, namely the planning, organizing, mobilizing, recording, monitoring and accountability stages. 3) the internal control system applied to the management of the Tajun Traditional Village LPD cash office includes the establishment of clear responsibilities , adequate records, insurance of company assets and employees, separation of recording and storage of assets, separation of responsibilities, use of mechanical equipment, as well as independent inspection. 4) The effectiveness of the internal control system implemented in the Tajun Village LPD cash office is considered effective based on the elements of internal control that are carried out in accordance with the criteria for achieving effective goals. Keywords: effectiveness, internal control system, management